Overstory structure and detrital dynamics of ponderosa pine forests: insights into fire behavior and its carbon consequences - Hall, Sonia A., author; Burke, Ingrid C., advisor; Vonder Harr, Thomas, committee member; Kaufmann, Merrill, committee member; Hobbs, N. Thompson, committee member (Colorado State University. Libraries, 2005)
Large, stand-replacing fires in the ponderosa pine forests of the Colorado Front Range have raised questions about long-term changes in fire severity and the controls on fire behavior. It is widely believed that fire suppression has contributed to fuel accumulation and, consequently, has caused severe fires. My goal was to provide methodological insights into (a) estimating overstory structure, and (b) the relation between fuels and fire behavior, and ecological insights into (c) these forests' detrital dynamics. I used lidar data to estimate biomass structure. I successfully estimated stand height, total aboveground biomass, basal area and foliage biomass. These technologies showed potential for estimating tree density, canopy base height and canopy bulk density, though more extensive datasets are needed to describe these relationships. These spatially explicit estimates are useful for quantifying carbon stocks and as inputs for fire behavior models. I analyzed the sensitivity of simulated crown fire hazard to variations in the inputs characterizing surface and canopy fuels. The simple simulation model used predicted that it was harder for a fire to reach the canopy than it was for it to move horizontally through it, suggesting that active crown fire hazard was particularly sensitive to the description of the surface fuels and to canopy base height. I described the long-term dynamics of detrital pools (dead wood, litter, duff). Woody detritus accumulated quickly after a fire, as dead material fell. This peak then decomposed before pool size increased again as new material fell. Litter accumulated monotonically, and was most strongly related to canopy cover. Duff was the hardest pool to predict. Topographical and soils characteristics did not appear to constrain these dynamics. The magnitude and timing of changes in detrital pools provide estimates of carbon sequestered in these pools, and inform the debate on whether present fires are outside the historical range of variability. My studies provide a framework for estimating carbon stocks and inform the debate on the controls over fire behavior. I highlight the importance of surface fuels in controlling crown fire hazard, and quantify the magnitude and timing of changes in detrital mass in these forests.
Keywords: ecology; forestry